Poetry of Spatial Contrast in the Poetry Majed Al-Hassan - Alaa Kadhim Rupa, Assist. Lect. (lark, 2022)
The goal of this study is to investigate Majid Al Hassan’s poetry for its use of spatial contrast. The purpose of this study is to derive its structure and manifestations, regardless of the limitations of abstract stylistic phenomena or the surface form of poems. The objective of this study is to demonstrate the element’s functional, artistic, and aesthetic value in poetry, as well as to interpret this selection in contrast construction. Along with the fundamental concepts that shaped it, most notably the visionary contradiction that culminated in the poet’s genuine vision. The study examines the poetic contrast in (Majid Al- Hassan’s) poetry by monitoring and analysing its function horizontally within a single text and vertically within texts belonging to the same group or poetic group, by employing the most urgent antonyms, and by identifying its various patterns and manifestations in poetry. Understanding it from the inside and revealing its contradictory secrets contributes to the transmission of a unique poetry that is inextricably linked to the text’s structures and connotations, which extend beyond the superficial structure to the deep structure capable of establishing a balance between the poet’s interior and exterior, and in a gradation that corresponds to the poet’s developing psychological state and the tension that underpins his relationship with things. Additionally, he discusses them from a philosophical standpoint.